CXCR3 CHEMOKINE RECEPTOR EXPRESSION ON PERIPHERAL BLOOD B-CELL SUBSETS IN PATIENTS WITH CHRONIC HEPATITIS C - N. A. Arsentieva; I. V. Kudryavtsev; D. S. Elezov; A. V. Semenov; E. V. Esaulenko; V. V. Basina; Areg A. Totolian (Медицинская иммунология)
Abstract. Present study was aimed to perform a quantitative determination of B lymphocyte subpopulations, i.e., B1, B2, memory B cells and CXCR3-positive B cells in peripheral blood of nineteen patients with chronic hepatitis C (HCV) and thirty-two healthy blood donors. Phenotyping of B cell subsets was performed by means of flow cytometry, using a combination of specific monoclonal antibodies, i.e., CD5-FITC/CD27-PC7/CXCR3-APC/CD19-APC-AF700/CD45-APC-AF750. Total numbers of B-lymphocytes and their subpopulations in peripheral blood of HCV-infected patients did not differ from appropriate values in control group. Meanwhile, expression of CXCR3 chemokine receptor in HCV patients proved to be significantly increased in all subsets of B cells. These results suggest a possible involvement of CXCR3-positive B cells into pathogenesis of chronic HCV infection.